2020
DOI: 10.1038/s41598-020-62420-1
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of intrauterine Bisphenol A exposure on pregnancy and expression of miRNAs related to heart development and diseases in animal model

Abstract: this study aimed to examine the impact of BpA exposure on pregnancy and foetuses on cardiac tissues and the expression of cardiac microRnAs (miRnAs) related to heart development and diseases. Pregnancy is known to be the "critical windows" in determining the offspring physical and cells development in their life after birth. The increment of the risk of cardiovascular disease (CVD) in a later stage of life has been reported by few studies demonstrated from prenatal exposure of BpA. BpA has been shown to alter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…Hu et al (2016) demonstrated that the increased myocardial collagen content in mice exposed to BPA is associated with MAPK ERK1/2 signaling pathway activation and with increased expression of the profibrotic factor TGF-β1. Also, prenatal exposure to BPA leads to fibrosis in fetal heart that was not associated with hepatotoxicity (Rasdi et al, 2020). Our study showed that short-term BPA exposure enhances the gene expression of CTGF while TGF-β1 was upregulated in the malnourished background only.…”
Section: Discussionmentioning
confidence: 55%
“…Hu et al (2016) demonstrated that the increased myocardial collagen content in mice exposed to BPA is associated with MAPK ERK1/2 signaling pathway activation and with increased expression of the profibrotic factor TGF-β1. Also, prenatal exposure to BPA leads to fibrosis in fetal heart that was not associated with hepatotoxicity (Rasdi et al, 2020). Our study showed that short-term BPA exposure enhances the gene expression of CTGF while TGF-β1 was upregulated in the malnourished background only.…”
Section: Discussionmentioning
confidence: 55%
“…B. Rasdi et al, 2020) and decrease (Belcher et al, 2015) blood pressure in rodent models. Although this discrepancy may be attributed to experimental design, which include different doses, treatment duration, and animals of differing age.…”
Section: Effects Of Bpa On Blood Pressure Regulation and Cardiovascmentioning
confidence: 95%
“…BPA‐exposed female offspring were at increased risk for cardiomyopathy, and both male and female offspring were prone to myocardial degeneration with signs of inflammatory cell infiltration. Rasdi et al also reported an increase in maternal and fetal cardiac fibrosis following intrauterine BPA exposure (Rasdi et al, 2020). At higher BPA concentrations (50,000 μg kg −1 day −1 ), focal inflammation was observed in the cardiac tissue of pregnant mice, which coincided with slowing of cardiac electrical conduction and increased systolic and diastolic pressure relative to vehicle control (Valokola et al, 2019).…”
Section: Bisphenol‐amentioning
confidence: 96%
See 1 more Smart Citation
“…Bisphenol A has become one of the most intensively manufactured chemicals in the world due to demonstrating the finest properties for plastic production (Noszczyńska and Piotrowska-Seget 2018 ). Numerous studies have investigated BPA effects on the human body and animals (Zhu et al 2015 ; Quesada et al 2002 ; Braun et al 2009 ; Izzotti et al 2009 ; Pfeifer et al 2015 ; Leung et al 2017 ; Maćczak et al 2017 ; Pinney et al 2017 ; Tian et al 2018 ; Grandin et al 2019 ; Özel et al 2019 ; Gao et al 2020 ; Rasdi et al 2020 ; Tassinari et al 2020 ; Wu and Seebacher 2020 ; Wu et al 2020a ; Pan et al 2020 ). Since BPA has a comparable structure to that of natural estrogen 17β-estradiol, it can bind to ERα and ERβ, though with 1000-fold less affiliation than estradiol (Gray et al 2004 ; vom Saal and Hughes 2005 ; Takayanagi et al 2006 ; Gray et al 2004 ; vom Saal and Hughes 2005 ; Takayanagi et al 2006 ).…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%